A high dynamic range structured light means for the 3D measurement of specular surface. (August 2017) - Song, Zhan; Jiang, Hualie; Lin, Haibo; Tang, Suming
Abstract: This paper presents a novel structured light approach for the 3D reconstruction of specular surface. The binary shifting strip is adopted as structured light pattern instead of conventional sinusoidal pattern. Based on the framework of conventional High Dynamic Range (HDR) imaging technique, an efficient means is first introduced to estimate the camera response function. And then, dynamic range of the generated radiance map is compressed in the gradient domain by introducing an attenuation function. Subject to the change of lighting conditions caused by projecting different structured light patterns, the structure light image with middle exposure level is selected as the reference image and used for the slight adjustment of the primary fused image. Finally, the regenerated structured light images with well exposing condition are used for 3D reconstruction of the specular surface. To evaluate performance of the method, some stainless stamping parts with strong reflectivity are used for the experiments. And the results showed that, different specular targets with various shapes can be precisely reconstructed by the proposed method. Highlights: A HDR-based binary SLS method was proposed for specular surface 3D reconstruction. An efficient means was introduced to calculate the camera response function. An attenuation function was used for dynamic range compression in gradient domain. The fused images were adjusted by the middle exposure-level SLS images. The final SLS images can realize accurate 3D reconstruction of specular surfaces.